Detection of catecholamines and metanephrines by radio-immunoassay in canine plasma - Francis, Roland C. E.; Pickerodt, Philipp A.; Salewski, Lothar; Boemke, Willehad; Hoehne, Claudia (Veterinary Journal, 2010)
This study investigated the applicability of two human radio-immunoassays (RIA) to detect epinephrine (EPI), norepinephrine (NE), and their O-methylated metabolites metanephrine (MN) and normetanephrine (NMN) in canine plasma. The analysis yielded a positive correlation between metabolites and their respective parent compounds: EPI and MN (r = 0.63), NE and NMN (r = 0.47), as well as between parent compounds, EPI and NE (r = 0.48), and between metabolites MN and NMN (r = 0.71). Moreover, EPI (r = 0.99) and NE (r = 0.77) concentrations determined by RIA did correlate positively with high pressure liquid chromatography (HPLC). However, there was limited agreement between both methods. It was concluded that complete validation tests for accuracy, precision and agreement are needed before this RIA can be applied to quantify catecholamines, metanephrine, and normetanephrine in canine plasma. The assay may prove to be a potential alternative to HPLC or tandem mass spectrometry in the work-up of pheochromocytoma and the detection of overall sympathetic activity in dogs. © 2008 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Catecholamine; Dog; Metanephrine; Normetanephrine; Radio immunoassay